GAMBARAN PENGETAHUAN REMAJA PUTRI TENTANG PREMENSTRUASI SYNDROME DI SMP NEGERI 29 PEKANBARU - Gasril, Pratiwi; Devita, Yeni; Putri, Erin Erana (Sistem Informasi, 2019)
Knowledge basically consists of a number of facts and theories that allow a person to be able to solve its problems. Pre Menstrual Syndrome is a symptom serampaian appearance before the menstrual cycle that is affecting the lifestyle and work. Know the description of knowledge about the young women Premenstrual Syndrome in Students SMPN29 Pekanbaru The study design is a form of design which is commonly used in conducting the research procedure. With a total sample of 99 respondents. The research instruments consisted of a questionnaire containing a questionnaire. The analysis is univariate analysis. Obtained results showed average average level of knowledge of premenstrual syndrome of the third level of knowledge the most is the level of knowledge was that (195.65%). From these values obtained concluded that the hypothesis is accepted penelitain mean average level of knowledge of premenstrual syndrome of the third level of knowledge the most is the level of knowledge was that (195.65%).